2017
DOI: 10.3389/fnhum.2017.00569
|View full text |Cite
|
Sign up to set email alerts
|

Motor Unit Activity during Fatiguing Isometric Muscle Contraction in Hemispheric Stroke Survivors

Abstract: Enhanced muscle weakness is commonly experienced following stroke and may be accompanied by increased susceptibility to fatigue. To examine the contributions of central and peripheral factors to isometric muscle fatigue in stroke survivors, this study investigates changes in motor unit (MU) mean firing rate, and action potential duration during, and directly following, a sustained submaximal fatiguing contraction at 30% maximum voluntary contraction (MVC). A series of short contractions of the first dorsal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
2
15
1
Order By: Relevance
“…Individuals with stroke, however, showed greater decreases in voluntary activation (Figure 3), less increase in EMG RMS, and less motor unit rate modulation (Figure 8) compared to the controls. These metrics indicate some combination of decreases from descending motor command and excitatory afferent inputs, as well as increases from inhibitory afferent inputs, to the motoneuron (Gandevia, 2001; Riley and Bilodeau, 2002; Knorr et al, 2011; Bowden et al, 2014; McManus et al, 2017). We also observed that greater increases in blood flow correlated with longer task duration only for the control group (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with stroke, however, showed greater decreases in voluntary activation (Figure 3), less increase in EMG RMS, and less motor unit rate modulation (Figure 8) compared to the controls. These metrics indicate some combination of decreases from descending motor command and excitatory afferent inputs, as well as increases from inhibitory afferent inputs, to the motoneuron (Gandevia, 2001; Riley and Bilodeau, 2002; Knorr et al, 2011; Bowden et al, 2014; McManus et al, 2017). We also observed that greater increases in blood flow correlated with longer task duration only for the control group (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies using transcranial magnetic stimulation have shown this may be due to a loss of excitatory descending drive most likely caused by the stroke-related lesions to the motor cortex (Foltys et al, 2003; Jang et al, 2017; Peters et al, 2017). Based on studies showing decreased excitability in descending motor pathways, it is not surprising that recent evidence suggests that in people with stroke, central fatigue is a more significant contributor to fatigability of the paretic leg muscles than for the non-paretic legs and healthy controls (Riley and Bilodeau, 2002; Hu et al, 2006; Klein et al, 2010; Knorr et al, 2011; Hyngstrom et al, 2012; Bowden et al, 2014; Rybar et al, 2014; Kuhnen et al, 2015; McManus et al, 2017). These studies attribute force generating deficits to baseline reductions in cortical commands, but they do not consider the impact of the build-up of metabolic by-products on muscle function that could contribute to increased fatigability of limb muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous sEMG and muscle force recordings during isometric muscle contractions may provide a more objective method of assessing local muscle fatigue in the clinic when compared with subjective mechanical techniques. Changes in the amplitude and the mean/median frequency of the sEMG signal can also provide insight into the relative prevalence of central 5 and peripheral fatigue 6 in neuromuscular disorders ( 40 ). An inability to sustain a voluntary, submaximal muscle contraction combined with a minimal decrease in the sEMG median frequency could indicate that the impairment is central in origin, arising from a suboptimal voluntary drive from brain to muscle.…”
Section: Background and Applicationsmentioning
confidence: 99%
“…It is likely that this imbalance of excitation and inhibition also causes changes in the potentiation and firing properties of the motor neurons themselves, ultimately leading to an impaired lower motor neuron recruitment which is remarkably biased towards the paretic side, inducing spasticity, high fatigability, and low motor unit recruitment rate 20,21 . A hyperactive clonus has sometimes been hypothesized to be induced by the seemingly chaotic reorganization of the supraspinal centers' patterning spinal structure, and haphazard pairing of the different interneuronal types driving type I and type II fibers with their presynaptic centers 22 .…”
Section: Stroke Affects Skeletal Muscle and Physical Activitymentioning
confidence: 99%
“…Other means to assess motor function after neurological injury involve the investigation of muscular synergies using surface electromyographic recordings 20,[45][46][47] . These methods require technical skill which involves mathematical computation and decomposition of EMG data, which proves sufficient for the evaluation of synergistic impairments in post-stroke patients, but is of little use in the experimental setting, where the most common models are the rodent models.…”
Section: Assessment Of Gait Deficit After Strokementioning
confidence: 99%